Human immune responses in cryptosporidiosis - Borad, Anoli (2010)
Immune responses play a critical role in protection from, and resolution of, cryptosporidiosis. However, the nature of these responses, particularly in humans, is not completely understood. Both innate and adaptive immune responses are important. Innate immune responses may be mediated by Toll-like receptor pathways, antimicrobial peptides, prostaglandins, mannose-binding lectin, cytokines and chemokines. Cell-mediated responses, particularly those involving CD4(+) T cells and IFN-γ play a dominant role. Mucosal antibody responses may also be involved. Proteins mediating attachment and invasion may serve as putative protective antigens. Further knowledge of human immune responses in cryptosporidiosis is essential in order to develop targeted prophylactic and therapeutic interventions. This review focuses on recent advances and future prospects in the understanding of human immune responses to Cryptosporidium infection.